Total phenolic content, antioxidant and antidiabetic properties of seed coats of selected beans and testa of coconut (Cocus nucifera L.) - Adetola, Adekola Khadijat (2017)
Diabetes mellitus is one of the most common metabolic disorders affecting the global population; management of this disorder still remains inadequate owing to the side effects of synthetic hypoglycaemic drugs available. This study aims at comparing the seed coats of four varieties of beans (red kidney bean, red bean, black-eyed pea, black bean) and testa of coconuts (mature and tender coconut) in terms of their antioxidant and antidiabetic properties. Hundred (100) gram portions of the milled bean seed coats and coconut testas were soaked, centrifuged and filtered to obtain crude extracts. Quantification of the phenolic acids and flavonoids in the extracts was carried out using high performance liquid chromatography coupled with diode array detection. The total phenolic content, total flavonoid content, antioxidant potentials (DPPH, ABTS and FRAP) and the α-amylase and α-glucosidase inhibitory activities of the crude extracts were studied in vitro. The results showed that the red kidney bean seed coat (RKB) {DPPH IC50=63.60±3.50 μg/mL, ABTS IC50=111.30±0.60 μg/mL, FRAP=204.71±2.87 mmol} and tender coconut testa (TCO) {DPPH IC50=47.40±7.00 μg/mL, ABTS IC50=125.70±6.70 μg/mL, FRAP=546.10±36.90 mmol} exhibited the highest antioxidant activities. Both extracts had also shown strong inhibition towards α-glucosidase activity (RKB, IC50=19.90±5.67 and TCO, IC50=4.84±1.43 μg/mL) and followed by mild inhibition towards α-amylase activity (RKB, IC50=120.5±15.4 and TCO, IC50=532.8±68.0 μg/mL). The total phenolic content of RKB seed coat and TCO testa extracts were 21.80±0.50 and 44.607±0.56 mg gallic acid equivalents per gram of seed coat while the flavonoid contents were 24.38±1.22 and 67.597±7.00 mg quercetin equivalents per gram of seed coat respectively. The chromatography results showed that the extracts contained appreciable level of some phenolic acids (0.01±0.01 - 5.747±0.54mg/g) and flavonoids (0.05±0.00 - 7.25±0.06 mg/g) including gallic acid, ellagic acid, caffeic acid, chlorogenic acid, quercetin, catechin, epigallocatechin gallate and rutin. In the in vivo study, antidiabetic effects of TCO and RKB on streptozotocin induced diabetic rats were evaluated using various biochemical parameters. Fortynine (49) rats were randomly divided into seven groups of seven rats each for normal control, diabetic untreated and five diabetic treated groups. Administration of extracts at a dose of 200 and 400 mg/kg body weight (b.wt.) were carried out daily for 14 days. The results showed that both TCO and RKB extracts at the different doses were able to significantly (p<0.05) reduce hyperglycaemia. Infact, TCO demonstrated the most remarkable reduction of 1.5 fold decrease at the dose of 200 mg/kg b.wt when compared to the normal control group. Treatments using these two extracts also reduced the levels of cholesterol, urea, bilirubin, creatinine, alanine transaminase (ALT), aspartate transaminase (AST) and total protein by trace amounts. These results suggest that red kidney bean seed coat and tender coconut testa would have higher potential as nutraceuticals and could serve as natural alternative sources for antidiabetic remedy.